Modular Motion-Structure Design Model for Planetary Surface Sampling - Qian Li; Lanlan Xie; Junping Li (International Journal of Aerospace Engineering)
Because there are less restrictions in space, a variety of different movement patterns and equipment structures may be used during the process of planetary surface sampling. Traditionally, the optimal analysis for surface sampling is focused on specific equipment structures and movements; in contrast, a new modular motion-structure design model for surface sampling, which is a more flexible model, is discussed in this paper. By establishing and combining two basic module groups, namely, the motion group and the structure group, this new design model can define and analyse multiple movement patterns and structures. For the motion group, calculating the sampling trajectory is the main purpose, in which there are two basic modules: tridimensional uniform rectilinear movements and tridimensional uniform circular movements. The two basic motion modules can be freely combined in a given coordinate system to simulate a random sampling trajectory. The structure group contains a series of curved and flat plates, which can be defined by a set of unified parameters (including section, extension, and cutting parameters). By assigning different values to these parameters, the curved or flat plates can represent different external shapes. The different structures of the various pieces of surface sampling equipment can be simulated by combining these different plates. In addition to defining these basic modules, analysing the coupling among different modules, which can be simplified to the relationship between velocity and surface, plays an important role in establishing this design model. Based on the modular design theory, this new model will not only reduce the difficulty of analysis but also improve accuracy for planetary surface sampling.